Glyphosate Resistance of C3 and C4 Weeds under Rising Atmospheric CO2 - Fernando, Nimesha; Manalil, Sudheesh; Florentine, Singarayer K.; Chauhan, Bhagirath S.; Seneweera, Saman (Frontiers in Plant Science, 2016)
The present paper reviews current knowledge on how changes of plant metabolism under elevated CO2 concentrations (e[CO¬2]) can affect the development of the glyphosate resistance of C3 and C4 weeds. Among the chemical herbicides, glyphosate, which is a non-selective and post-emergence herbicide, is currently the most widely used herbicide in global agriculture. As a consequence, glyphosate resistant weeds, particularly in major field crops, are a widespread problem and are becoming a significant challenge to future global food production. Of particular interest here it is known that the biochemical processes involved in photosynthetic pathways of C3 and C4 plants are different, which may have relevance to their competitive development under changing environmental conditions. It has already been shown that plant anatomical, morphological and physiological changes under e[CO¬2] can be different, based on (i) the plant’s functional group, (ii) the available soil nutrients and (iii) the governing water status. In this respect, C3 species are likely to have a major developmental advantage under a CO¬2 rich atmosphere, by being able to capitalize on the overall stimulatory effect of e[CO¬2]. For example, many tropical weed grass species fix CO2 from the atmosphere via the C4 photosynthetic pathway, which is a complex anatomical and biochemical variant of the C3 pathway. Thus, based on our current knowledge of CO2 fixing, it would appear obvious that the development of a glyphosate-resistant mechanism would be easier under an e[CO¬2] in C3 weeds which have a simpler photosynthetic pathway, than for C4 weeds. However, notwithstanding this logical argument, a better understanding of the biochemical, genetic and molecular measures by which plants develop glyphosate resistance and how e[CO2] affects these measures will be important before attempting to innovate sustainable technology to manage the glyphosate-resistant evolution of weeds under e[CO2]. Such information will be of essential in managing weed control by herbicide use, and to thus ensure an increase in global food production in the event of increased atmospheric [CO2] levels.